Resenha: Gary L. Francione & Robert Garner: The Animal Rights Debate: Abolition or Regulation? - da Trindade (UFSM), Gabriel Garmendia; Nunes (UNIPAMPA), Lauren de Lacerda (Intuitio, 2011)
Esta é a resenha do livro The Animal Rights Debate: Abolition or Regulation?, escrito por Gary L. Francione e Robert Garner. A respectiva obra versa sobre a questão do tratamento moral a ser concedido aos animais não-humanos. Neste sentido, a Abordagem Abolicionista dos Direitos dos Animais de Francione e o Protecionismo Animal proposto por Garner são analisados por ambos os autores. Assim, questões de cunho teórico e prático abordadas no livro serão repensadas e avaliadas na presente resenha. This is a review of the book written by Gary L. Francione and Robert Garner whose title is The Animal Rights Debate: Abolition or Regulation?. The respective work deals with the case about the moral treatment to be granted for nonhuman animals. In this sense, Francione’s Abolitionist Approach to Animal Rights and Garner’s Animal Protectionism will be analyzed by both authors. Therefore, theoretical and practical questions approached in the book will be rethought and evaluated in the current review.